The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2014
DOI: 10.1007/s00264-014-2290-5
|View full text |Cite
|
Sign up to set email alerts
|

Effect of tibial drill-guide angle on the mechanical environment at bone tunnel aperture after anatomic single-bundle anterior cruciate ligament reconstruction

Abstract: Purpose The tibial drill-guide angle in anterior cruciate ligament (ACL) reconstruction influences the tunnel placement and grafttunnel force, and is potentially associated with post-operative tunnel widening. This study aimed to examine the effect of the drill-guide angle on the stress redistribution at the tibial tunnel aperture after anatomic single-bundle ACL reconstruction. Methods A validated finite element model of human knee joint was used. The tibial tunnel with drill-guide angle ranging from 30°to 75… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 24 publications
0
12
0
Order By: Relevance
“…Several studies (Schechtman and Bader, 1997;Jagodzinski et al, 2005;Yao et al, 2014;Srinivas et al, 2016;Srinivas et al, 2016) have investigated the factors that might cause tunnel enlargement and graft failure. Srinivas et al (Srinivas et al, 2016) found that the enlargement of femoral tunnel and tibial tunnel varied with different methods of fixation.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies (Schechtman and Bader, 1997;Jagodzinski et al, 2005;Yao et al, 2014;Srinivas et al, 2016;Srinivas et al, 2016) have investigated the factors that might cause tunnel enlargement and graft failure. Srinivas et al (Srinivas et al, 2016) found that the enlargement of femoral tunnel and tibial tunnel varied with different methods of fixation.…”
Section: Introductionmentioning
confidence: 99%
“…Schechtman et al (Schechtman and Bader, 1997) reported a linear relationship between the stress and the number of cycles of tendons to fatigue failure. Few studies demonstrated that tunnel orientation might influence tunnel enlargement and graft failure (Jagodzinski et al, 2005;Yao et al, 2014). Specifically, Yao et al (Yao et al, 2014) quantified the effects of tibial tunnel drill-guide angle on the stress redistribution at the tibial tunnel aperture after ACLR, which potentially contributed to the tibial tunnel widening.…”
Section: Introductionmentioning
confidence: 99%
“…To simulate conventional ACLR, the original ACL was removed, and the femoral and tibial tunnels (diameter 7.5 mm) were created through the center of ACL insertion sites. The angles between the femoral tunnel axis and the axial and sagittal planes were 45 • and 25 • , respectively, and the angles between the tibial tunnel axis and the axial and sagittal planes were 65 • and 25 • , respectively (Yao et al, 2014). A four-strand hamstring tendon graft was simulated as being cylindrical in shape with a diameter of 7.5 mm and stiffness of 776 N/mm (Hamner et al, 1999).…”
Section: Simulation Of Conventional Aclr Using Circular Tunnelmentioning
confidence: 99%
“…Pena et al have previously shown the angle of the femoral tunnel primarily affects tension of the graft, while the tibial tunnel significantly affects laxity and meniscal stresses ( 35 ). For example, tibial drill-guide angles between 55 and 65 degrees have been proposed as optimal angles for proper stress redistribution ( 36 ). Moreover, the graft tension is vitally important as enough tension is required to maintain stability, while a mechanism has been proposed where too much tension leads to physeal compression and ultimately damage ( 33 ).…”
Section: Current Standard Of Care Does Not Address Individual 3d Geommentioning
confidence: 99%